INTEGRATION OF BALINESE, CHINESE AND EUROPEAN ORNAMENTS IN THE ARCHITECTURE OF PURI AGUNG KARANGASEM-BALI - I Nyoman Laba; Ida Ayu Gede Artayani; I Ketut Muka; I Made Mertanadi; I Wayan Sudana; Ni Made Rai Sunarini (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: This study aims to explain the form of integration of Balinese, Chinese and European ornaments in the architecture of Puri Agung Karangasem. Research methods: A qualitative descriptive method was implemented to explain the integration of ornaments in the architecture of Puri Agung Karangasem. Data collection techniques are observation, interviews, and documentation, while the data sources are ornaments on the architecture of the palace heritage, cultural experts, and community leaders. The Penglingsir Puri (Palace’s Elders) and Abdi Dalem Puri (Palace’s Courtiers) are key informants. Findings: The results showed that the forms of ornaments found at Puri Agung Karangasem could be divided into three, namely ornaments in traditional Balinese, Chinese, and European styles, resulting in a combination of the typical ornament forms of Puri Agung Karangasem. The three styles of ornament were integrated with each other, then developed by Balinese artists to create patra cina, patra olanda, karang sae, karang bentulu, and the visualization of a crowned lion as it is known today. Other integrations can be seen in the technique of making ornaments using casting techniques. Implications: The rulers of Puri Agung Karangasem in ancient times had cultural relations with people from China and Europe, reflected in the visualization of the integration of carved ornaments into the palace’s architecture.